A PRACTICAL APPROACH TO VISUAL DESIGN AND CONTENT MODIFICATION FOR A STUDENT EXCHANGE GUIDEBOOK - Erik Tanata; Datu, Yerly Arnold (Politeknik Ubaya, 2025)
This study examines the challenges faced by the Office of University X in promoting student exchange programs due to its ineffective guidebook. Using a descriptive method, data were collected through an online questionnaire (N=20 students), informal interviews with staff and students, document analysis, and library research. The small sample size resulted from a short data collection period (two to three weeks) and the heavy academic workload of senior students. Findings revealed weaknesses in the previous guidebook, including a plain monochrome design, lack of visuals, text-heavy content, and limited distribution. Consequently, only 40% of respondents were aware of the program, although 85% expressed interest. Guided by Cognitive Load Theory and Mayer’s Multimedia Learning Principles, the redesign applied evidence-based improvements: (1) mobile-first responsive layout, (2) high-contrast color and clear typography, (3) infographics and icons to aid comprehension, (4) concise, chunked content with bullet points, and (5) interactive elements such as clickable links and QR codes. Post-assessment results indicated strong positive responses: 80% of students found the new guidebook more engaging, 70% appreciated its visual appeal, and 100% agreed that infographics clarified complex information. Moreover, 80% reported increased motivation to join exchange programs after viewing the redesigned version. The study proposes three strategies for continued effectiveness: (1) active online distribution via portals and social media, (2) biannual updates with new data and testimonials, and (3) development of interactive tools such as chatbots or virtual info sessions. Strategic design improvements can thus enhance educational resources and reduce administrative burdens.